Lysine requirement of weaned piglets - S. Goethals; P. Bikker; J.H.M. Rijpert; B. Ampe; J.W. Spek; S. Millet (Animal)
Lysine, often referred to as the ‘first limiting amino acid’ in pig nutrition, plays a pivotal role in growth performance. Variability in lysine requirements arises due to factors such as age, sex and environmental conditions. Optimising pig health and production efficiency and minimising nitrogen excretion require accurate knowledge of estimated lysine requirements accounting for factors such as genetics, feeding practices, scientific advancements, and environmental considerations. This study aimed to determine standardised ileal digestible (SID) lysine requirements of weaned piglets (5–30 kg) based on a literature review using meta-analytical approaches. The literature review yielded 344 studies that were screened for title and abstract. In total, 41 experiments met the inclusion criteria, resulting in a dataset of 206 treatment means. Linear, quadratic and linear-plateau models were used to gain insight into the effect of SID lysine addition on average daily gain and feed efficiency for the combined dataset and separately for the individual experiments. Regression analysis showed a predominant linear increase in average daily gain and feed efficiency as an overall response to increasing lysine levels across both the combined dataset and individual experiments. Breakpoint estimation from the linear-plateau models was inconclusive, indicating that the optimal SID lysine requirement to maximise piglet growth performance likely exceeded the upper lysine levels tested in most studies, thus surpassing 1.3 g SID lysine per MJ net energy. This review indicates high values for the lysine requirement to achieve maximum growth performance. Results may suggest that piglet feed formulation should focus on an optimal dietary SID lysine to CP ratio, rather than SID lysine per kg of diet or unit of net energy. However, more research is needed to investigate this suggestion.